REPRESENTASI ORANG MANDAR DALAM REALITAS SOSIAL - Djamereng, Asni (Istiqra: jurnal hasil penelitian, 2022)
This research aims to discover and explain the Mandar people’s representation in semiotic studies. This research uses qualitative research methods using representation theory. The data in this research was collected through interviews, observation, and documentation. Then from this data, research was produced that showed that the representation of the Mandar community is a religious community. These accomplished and brave sailors maintain and uphold the customs and traditions of their predecessors and are very firm in keeping their promises. The research implications include that symbols should be provided at the borders of Polewali Mandar Regency, the government should increase the number of books regarding local cultural values in Polewali Mandar, regional symbols, and the history of Polewali Mandar